Religion in the lives of American adolescents - Fritsch, Melissa (2003)
The purpose of the project is to research the shape and influence of religion and spirituality in the lives of U.S. adolescents; to identify effective practices in the religious, moral, and social formation of the lives of youth; to describe the extent to which youth participate in and benefit from the programs and opportunities that religious communities are offering to their youth; and to foster an informed national discussion about the influence of religion in youth's lives, in order to encourage sustained reflection about and rethinking of our cultural and institutional practices with regard to youth and religion.Summary of research findings on the influence of religion on the lives of U.S. adolescents.The National Study of Youth and Religion, funded by Lilly Endowment Inc. and under the direction of Dr. Christian Smith, professor in the Department of Sociology, is based at the Odum Institute for Research in Social Science at The University of North Carolina at Chapel Hill. This four-year research project began in August 2001 and will continue until August 2006